(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The "new" literary trend known as "new historicism," which gained popularity in the 1980s, emphasises personal histories to question the conventional perspective of the past. Authors popularised this approach. Since New Historicists maintain that there is more than one version of history, their primary focus is on analysing different interpretations of past events. This article aims to examine When We Were Orphans by Kazuo Ishiguro via the theoretical framework of the New Historicist movement and its critique of traditional historiography. Specifically, this analysis will focus on time, memory, and narrative technique to demonstrate how history is subjectively narrated in various ways and how personal and public histories are intertwined. Key ideas discussed in this piece centre on New Historicism, historical representation, the historicity and textuality of historical writings, memories, and Kazuo Ishiguro